Penerapan Metode Naïve Bayes Untuk Mengetahui Kualitas Air Di Jakarta - Yunita Sartika Sari (Fakultas Ilmu Komputer, 2021)
Water is a chemical compound that is needed for the survival of living things on earth. The largest area on planet earth is water which covers almost 71% of the area on earth. Water is also a very important substance on earth that is needed by all living things ranging from plants, animals and humans. It is necessary to monitor and treat the environment around the water source so that it can produce clean water quality. In this study, the Naïve Bayes algorithm is applied to determine water quality in the Jakarta area and produces an accuracy rate of water classification results in the DKI Jakarta area of 50.6%.